Implementation of Guidance and Counseling Principles in Education - Addahri Hafidz Awlawi, Wisda Rahmadinur, Imratul Handayani (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This article discusses the Principles and Principles of Guidance and Counseling in running individual service programs. Based on the discussion of the principles and principles of Guidance and Counseling is a guideline and direction that must be done by counsellors to individuals. This principle will have a positive impact to support the success in the counseling program. The program will be flexible as well as relax the individual. Individuals will give different and unique thoughts that is the task of the counsellor to help the individual in getting to know himself. This principle also makes it clear that the person providing the service must be competent and educated accordingly.BK principle is also directed in accordance with the desired target. with the principle is the basic law in carrying out guidance and counseling services.Basic services will help counselors and individuals to move regularly and comply with regulations. This principle is expected to assist individuals in taking a stand on the issue.